THE EFFECTIVENESS OF MONETARY POLICY AND ITS IMPACT ON SUSTAINABLE DEVELOPMENT IN IRAQ FOR THE PERIOD (2003-2024): PROBLEMS AND SOLUTIONS - Haqi Ameen Tomas; Naseer Faisal Najm; Amel Swadi Kashmar (Scholars Digest Publishing, 2026)
Sustainable development has become the main concern of all global economies, and all countries are directing their economies to achieve the goals of sustainable development, allocating all their resources and economic policies to achieve this aim. Here, the significant and effective role of monetary policy in achieving these goals becomes evident. The study examined the most important tools of monetary policy in Iraq and how to direct these tools towards achieving sustainable development goals for the period (2003-2024), as well as the key problems and obstacles facing these policies. A set of conclusions and recommendations was reached that could contribute to making monetary policy more effective in achieving sustainable development goals.
Keywords: Sustainable development, monetary policy, GDP, unemployment, inflation, exchange rate.